Augmented Reality in the Application of 3 Dimensional Objects as Laboratory Equipment - Primajati, Gilang (Balai Publikasi Indonesia, 2024)
In today's developing era, quite a few schools still have limitations or lack of learning media. So technology is needed to support the learning process so that it is easier for students to learn both online and offline. This research aims to create and add Augmented Reality-based learning media at SMA Negeri 1 Plampang. The learning media created is a chemistry practical learning application using the Android platform which will be implemented in the chemistry textbook for class XMIPA students at SMA Negeri 1 Plampang. Augmented Reality technology makes it possible to combine the virtual world and the real world in real time. So it will be able to provide a real learning experience. By applying Augmented Reality to the Chemistry textbook, students will be able to get to know the chemistry practical tools displayed through the application without needing to look directly into the chemistry laboratory. The research method used is the ADDIE method which consists of analysis, design, development, implementation and evaluation stages. This method will produce output in the form of an Android-based application that uses Augmented Reality technology to display 3D objects for chemistry practical tools. Based on the results of the questionnaire or questionnaire that was given to respondents, the result was that the application that had been created was feasible and could be used as a learning medium that would be used at SMA Negeri 1 Plampang in the Chemistry subject class X-IPA CHAPTER 1